Medição e modelagem da resposta de um sensor de pig perfilométrico sob diferentes solicitações dinâmicas - Medeiros, Jarbas Santos (2013)
Ensure the integrity of the pipeline network is an extremely important factor in the oil and gas industry. The engineering of pipelines uses sophisticated robotic inspection tools in-line known as instrumented pigs. Several relevant factors difficult the inspection of pipelines, especially in offshore field which uses pipelines with multi-diameters, radii of curvature accentuated, wall thickness of the pipe above the conventional, multi-phase flow and so on. Within this context, appeared a new instrumented Pig, called Feeler PIG, for detection and sizing of thickness loss in pipelines with internal damage. This tool was developed to overcome several limitations that other conventional instrumented pigs have during the inspection. Several factors influence the measurement errors of the pig affecting the reliability of the results. This work shows different operating conditions and provides a test rig for feeler sensors of an inspection pig under different dynamic loads. The results of measurements of the damage type of shoulder and holes in a cyclic flat surface are evaluated, as well as a mathematical model for the sensor response and their errors from the actual behavior